Analisis Perilaku Konsumen dalam Membeli Daging Sapi Di Kota Kefamenanu Kabupaten Timor Tengah Utara - Resty Maria Bainhana; Stefanus Sio; Kristoforus W. Kia (JAS, 2021)
The research was conducted at the TTU Slaughterhouse (RPH) and Pasar Baru Kota Kefamenanu from October to November 2018. This study aims to look at consumer behavior in buying meat, both in terms of meat quality, consumer tastes in choosing meat, and also price. The method used is a survey method with descriptive approaches and correlational methods. The descriptive method aims to make descriptions or descriptions of the facts, characteristics, and relationships of the phenomena being investigated in a particular population or area in a systematic, factual, and accurate manner. The correlational method is a continuation of the descriptive method which aims to study the statistical relationship between the variables under study. The variables observed were consumer tastes where beef buyers both in the new market and at the Kefamenanu City Slaughterhouse (RPH) prefer fresh beef with a slightly brownish-red color with fat color attached to white meat, less fatty meat, distinctive aroma of the meat, or odorless and smooth meat texture. Most consumers choose has to beef because it has a soft texture and contains a little bit of fat, and most consumers who buy beef for business, be it for shops, selling meatballs or salome with a range of buying meat between 1 to 4 kg and above every day. For the reason that consumer prices do not feel influential in buying beef, but the supply system is important in purchasing meat and the satisfaction of prices is felt by consumers today due to the availability of sufficient beef at affordable prices.